Development of SLOC, CC, SQL Complexity Methods to Measure the Level of Similarity Complexity of Software Modules - Made Agus Putra Subali; I Gusti Rai Agung Sugiartha; I Putu Aditya Putra (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2023)
Software metrics are often used to reflect vulnerabilities in program code to measure the complexity of each software module. Knowing the complexity of each software module is an important thing to do because the project manager can analyze defects that may occur, costs spent, work schedules, and the resources needed. In this research, we aim to apply the SLOC, CC, SQL Complexity method in measuring the level of similarity of complexity between software modules by paying attention to the level of similarity of the syntactic structure of program logic and SQL commands, by knowing the similarity between software modules the project manager can predict the effort required. Based on the results of the level of equality for the eight modules, an average of 90% was obtained. The high results are due to the third feature used having a high level of similarity. In further research, other features will be added and weighting will be given to each feature.